The Land of Complexity 19th and 20th Century Northern Borneo SocioDemographic History: A Review - Nour M. Adriani; Labibatussolihah; Mohammad Refi Omar Ar Razy; Andi Suwirta (Jurnal Sosial Humaniora, 2021)
North Borneo has always been the object of international interests and politics.This situation is the effect of socio-demographic plurality that led to theabsence of a cohesive socio-political identity that can unite them together. Thisstudy aims to analyze the social demographic history of the people of NorthBorneo (Kalimantan) in the 19th and 20th centuries to understand thecomplex geopolitics in the region during the decolonialisation process in thepost-Second World War. Using a literature review, there are some pointsconcluded, first, the Malay Sultanate of Brunei had dominated the politicalstructure of the area that influenced the foundation of the Malay social systemin North Borneo for the following centuries. Second, the colonial project ofJames Brooke changed the social order in North Borneo with the significantpresence of non-Malay groups such as the Chinese until the mid-20th century.Third, the Japanese occupation during the Second World War had broughtnationalism among the natives. This spirit had led to an attitude ofethnonationalism that makes it was challenging to build a cohesive nationalidentity among different ethnic groups there. Fourth, after the war, regionalconflicts due to the Cold War triggered differences in political systems amongthe new states that gained independence